2015
DOI: 10.1111/ped.12640
|View full text |Cite
|
Sign up to set email alerts
|

Burkitt lymphoma with unusual presentation: Acute pancreatitis

Abstract: Pancreatitis due to malignant infiltration is an uncommon condition in childhood. Pancreatic lymphomas constitute <2% of all non-Hodgkin lymphomas. Only six reported cases with various clinical presentation have been documented in the literature. Described herein is the case of a nine-year-old boy with abdominal pain, jaundice, emesis, weight loss, diarrhea, who developed hyperlipidemia and cholestasis. Pancreatitis was suspected due to high amylase and lipase. Computed tomography and magnetic resonance cholan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
0
9
0
3
Order By: Relevance
“…The literature also reported that BL can rarely involve the pancreas. [ 19 , 20 ] In addition, bone marrow involvement is encountered in under 10% of the cases at onset, but is more frequent in case of recurrence or with treatment resistance. [ 21 ] Of our 3 cases diagnosed with BL none presented bone marrow involvement, either the one with IV-stage BL, but in exchange that patient presented central nervous system metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The literature also reported that BL can rarely involve the pancreas. [ 19 , 20 ] In addition, bone marrow involvement is encountered in under 10% of the cases at onset, but is more frequent in case of recurrence or with treatment resistance. [ 21 ] Of our 3 cases diagnosed with BL none presented bone marrow involvement, either the one with IV-stage BL, but in exchange that patient presented central nervous system metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Primary Burkitt's lymphoma of the pancreas is extremely rare with only a few cases described in the literature; some of these cases describe a single mass lesion, whereas other cases describe diffuse pancreatic involvement . Primary pancreatic lymphoma has been described to cause bile and pancreatic duct dilatation and mimic acute cholestatic hepatitis, to present as acute pancreatitis, and also to induce temporary diabetes mellitus …”
Section: Discussionmentioning
confidence: 99%
“…1 Primary Burkitt's lymphoma of the pancreas is extremely rare with only a few cases described in the literature; some of these cases describe a single mass lesion, whereas other cases describe diffuse pancreatic involvement. [2][3][4][5] Primary pancreatic lymphoma has been BIFOCAL PANCREATIC BURKITT'S LYMPHOMA VOL. 45, NO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary pancreatic lymphoma represents less than 0.5% of all pancreatic masses in adults. Moreover, acute pancreatitis is a very rare initial presentation of non-Hodgkin lymphomas [5][6][7][8][9][10]. We present the case of a six-year-old girl diagnosed with Burkitt lymphoma who presented with obstructive jaundice and pancreatitis.…”
Section: Introductionmentioning
confidence: 99%